Microstructural Analysis of Au/TiO2-SBA-15 Nanocomposite. (1st May 2014) - Gondo, Takashi; Kaneko, Kenji; Nishiyama, Takeshi; Yamada, Kazuhiro; Saghi, Zineb; Barnard, Jonathan S.; Midgley, Paul A.
Abstract Properties of gold nanoparticles (AuNPs) are very different from bulk gold, in particular, highly dispersed AuNPs exhibit high catalytic activities on metal oxide supports. Catalytic activities of AuNPs are strongly dependent on: (i) size and morphology; (ii) synthesis methods; (iii) nature of the support; (iv) interaction between AuNPs and the support; and (v) oxidation state of AuNPs in the synthesized catalysts. A goal is to maintain the size and to prohibit aggregation of AuNPs, since aggregations deteriorate catalytic activities. Some strong interactions are therefore required between AuNPs and their supports to prevent the movement of AuNPs. SBA-15 is a promising material for the support of AuNPs since it has ordered two-dimensional hexagonal pore channels, uniform pore size ranging from 5 to 30 nm, narrow pore size distribution, thick amorphous walls ranging from 3 to 6 nm, and high surface area. In this study, SBA-15, TiO2-SBA-15 and TiO2-SBA-15-AuNP nanocomposites were synthesized by the sol-gel method and microstructural characterizations were carried out by both X-ray diffraction analysis and electron microscopy.